Trends in Annual Survival of Steller’s Eiders Molting at Izembek Lagoon on the Alaska Peninsula, 1993–2006 - Frost, Charles J.; Hollmen, Tuula E.; Reynolds, Joel H. (ARCTIC, 2013)
Izembek Lagoon, located on the Alaska Peninsula, is an important molting area for the Pacific population of Steller’s Eiders (Polysticta stelleri) and was the site of consistent banding effort during 1993–2006. We used Pradel mark-recapture models to estimate annual survival and population growth rates for adult Steller’s Eiders molting at Izembek Lagoon. We designed 32 models that included effects of sex and year on survival, recapture rate, and seniority, as well as potential trends in survival and seniority. The top model incorporated a two-phase trend (1993–98, 1999–2003) in survival and seniority for each sex and fully sex- and year-specific recapture rates. Average annual adult survival was estimated at 0.86 (SE = 0.030) for females and 0.87 (SE = 0.018) for males. Average annual population growth rates since 1998 were estimated to be approximately 1.0 for both sexes. A brief warming event in the Pacific Decadal Oscillation (1997–98) coincided with the lowest estimates of annual survival, while a subsequent return to cooler conditions in the Bering Sea coincided with the highest estimates and an increasing trend in annual survival. La lagune d’Izembek, située dans la péninsule de l’Alaska, constitue une aire de mue importante pour la population d’eiders de Steller (Polysticta stelleri) du Pacifique. Elle a fait l’objet de travaux de baguage soutenus entre 1993 et 2006. Nous nous sommes servis des modèles de marquage et de recapture de Pradel pour estimer les taux de survie et d’accroissement de la population d’eiders de Steller adultes en période de mue à la lagune d’Izembek. Nous avons conçu 32 modèles qui compre-naient les effets du sexe et de l’année sur le taux de survie, le taux de recapture et l’ancienneté. Le meilleur des modèles comprenait une tendance diphasique (de 1993 à 1998, et de 1999 à 2003) en ce qui a trait aux taux de survie et d’ancienneté de chacun des sexes ainsi qu’en ce qui a trait aux taux de recapture entièrement en fonction du sexe et de l’année. Chez les adultes, le taux de ...